Quality Assessment of Skincare Products with Simple Additive Weighting Approach to Detect Illegal Skincare Products - Dudih Gustian; Ismi Nurhadianti Rusmana; Dede Sukmawan (INTERNATIONAL JOURNAL ENGINEERING AND APPLIED TECHNOLOGY (IJEAT), 2024)
The increasing public need for skincare products encourages manufacturers to innovate in creating products that suit consumer needs. However, with easy access to information in the digital era, new problems have arisen related to the diversity of skincare products on the market, including the rise of fake products containing dangerous ingredients. This research uses the SAW method to evaluate the quality of skincare products based on predetermined criteria. With a large female population in Indonesia and significant growth in online sales of skincare products, this research contributes to helping consumers choose safe and effective skincare products. It is hoped that using the SAW method can identify or reduce the risk of using fake skincare which can endanger skin health and cause serious dermatological problems. Therefore, a thorough understanding of skincare and the use of analytical methods such as SAW are important in the consumer decision-making process